Clays and Clay Minerals, Vol. 57, No. 2, 264–270, 2009. - Benhammou, Abdelaziz; Tanouti, Boumediene; Nibou, Lahbib; Yaacoubi, Abdelrani; Bonnet, Jean-Pierre (My University, 2009)
‘Ghassoul’ clay is a Mg-rich clay from Morocco which is of great industrial use and interest, but its characterization is still incomplete. The purpose of this study was to provide further details regarding the structure and characteristics of this important commercial clay mineral. Mineralogical and physicochemicalcharac terizations of the raw form of ‘Ghassoul’ clay from JbelGhassoulin Morocco, and of its <2 mm size fraction, purified and Na+-saturated, were carried out using X-ray diffraction (XRD), X-ray fluorescence (XRF), infrared spectroscopy (IR), and differential and thermogravimetric analysis (DTA/TG). The XRD data revealed that the raw Ghassoul clay consists mainly of a Mg-rich trioctahedral smectite, stevensite, together with quartz and dolomite. The IR spectra consisted of vibrations typical of trioctahedral smectites. The DTA/TG curves were also similar to those of trioctahedral smectites. Chemicalanal ysis confirms that this Mg-rich trioctahedral smectite is a stevensite characterized by a limited isomorphic substitution of Si4+ by Al3+. The thermalt ransformations examined by in situ XRD as a function of the firing temperature from 100 to 1200ºC indicated that stevensite was transformed to enstatite (MgSiO3) at temperatures >800ºC and that quartz was transformed to cristobalite when the temperature exceeded 1100ºC. These transformations were irreversible. The specific surface area and cation exchange capacity (CEC) of the ‘Ghassoul’ clay are 133 m2/g and 75 meq/100 g, respectively. The main exchangeable cation is Mg2+ (53 meq/100 g).
Mineralogical And Physicochemical Investigation Of Mg-smectite From Jbel Ghassoul, Morocco
gsccm57212-ben.pdf: 350KB
Keywords: Periodicals; Geology; Characterization; Ghassoul Clay; Smectite; Stevensite; Morocco